2018
DOI: 10.1186/s11671-018-2775-z
|View full text |Cite
|
Sign up to set email alerts
|

Tiny Rare-Earth Fluoride Nanoparticles Activate Tumour Cell Growth via Electrical Polar Interactions

Abstract: Localised extracellular interactions between nanoparticles and transmembrane signal receptors may well activate cancer cell growth. Herein, tiny LaF3 and PrF3 nanoparticles in DMEM+FBS suspensions stimulated tumour cell growth in three different human cell lines (A549, SW837 and MCF7). Size distribution of nanoparticles, activation of AKT and ERK signalling pathways and viability tests pointed to mechanical stimulation of ligand adhesion binding sites of integrins and EGFR via a synergistic action of an ensemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…This would depend on dendrimer size, surface molecule charge, reactivity, and concentration. For small nanoparticles (<10 nm), it has been found that rare-earth fluoride nanoparticles at low concentration stimulate proliferation of three human cell lines—A549, SW837, and MCF-7—through activation of EGFR and integrin signaling [77]. Native PAMAM G3 dendrimer molecule has about 3.2 nm diameter.…”
Section: Resultsmentioning
confidence: 99%
“…This would depend on dendrimer size, surface molecule charge, reactivity, and concentration. For small nanoparticles (<10 nm), it has been found that rare-earth fluoride nanoparticles at low concentration stimulate proliferation of three human cell lines—A549, SW837, and MCF-7—through activation of EGFR and integrin signaling [77]. Native PAMAM G3 dendrimer molecule has about 3.2 nm diameter.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to every drug, nanoparticles are, to a certain level, toxic [94]. For example, NPs, can translocate across biological barriers and affect secondary target organs [95], they can have adverse effects on certain cancer cells (e.g., activate cancer cells instead of damaging them) [96], agglomerate on the surface of other cells, such as endothelial cells [97] and platelets [98], or form cluster with a large HD [97], influencing their renal excretion resulting in an increased lifetime in the body. Therefore, efforts have to be dedicated to designing NPs to reduce their toxicity.…”
Section: Future and Perspectivesmentioning
confidence: 99%
“…The first is the increasing in size of the NPs which leads to a reduction of the role of the surface. The second is the migration of the OH groups from the NP's core to specific water clusters [30,56,57] which leads to reducing the total amount of Pr 3+ ions contacting with OH groups.…”
Section: Optical Spectroscopy and Luminescencementioning
confidence: 99%